2001
DOI: 10.1006/nimg.2001.0749
|View full text |Cite
|
Sign up to set email alerts
|

The Neural System Underlying Chinese Logograph Reading

Abstract: Written Chinese as logographic script differs notably from alphabets such as English in visual form, orthography, phonology, and semantics. Thus, research on the Chinese language is important to advance our understanding of the universality and particularity of the organization of language systems in the brain. In this study, we examine the neural systems associated with logographic reading using functional magnetic resonance imaging. Two experimental tasks were devised, one based on semantic decision and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

32
301
2
2

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 397 publications
(342 citation statements)
references
References 95 publications
(104 reference statements)
32
301
2
2
Order By: Relevance
“…Thus, our Chinese bilinguals were able to prepare the pronunciation of high-frequency Chinese words as early as 250 msec. Activation then shifted for both high-and low-frequency Chinese characters to the right prefrontal area (BA 10), an area identified in imaging studies of both English and Chinese [Fiez et al, 1999;Tan et al, 2001]. This result adds to the conclusion that Chinese may produce more right hemisphere processing than English [Tan et al, 2001].…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Thus, our Chinese bilinguals were able to prepare the pronunciation of high-frequency Chinese words as early as 250 msec. Activation then shifted for both high-and low-frequency Chinese characters to the right prefrontal area (BA 10), an area identified in imaging studies of both English and Chinese [Fiez et al, 1999;Tan et al, 2001]. This result adds to the conclusion that Chinese may produce more right hemisphere processing than English [Tan et al, 2001].…”
Section: Discussionmentioning
confidence: 59%
“…However, these studies have identified additional brain areas not often observed in alphabetic studies, especially left middle frontal areas (BA 9), additional right hemisphere cortical regions (BAs 47/ 45,7,40/39), and the right visual system [Tan et al, 2000[Tan et al, , 2001.…”
Section: Introductionmentioning
confidence: 95%
“…One previous study found that Chinese phonological processing activated bilateral thalamus, cerebellum, occipital lobe, and lingual gyrus (Kuo et al, 2004). Other studies also found that the right visual system (BA17/18/19) was involved in reading Chinese relative to reading English (Liu and Perfetti, 2003;Tan et al, 2001). These patterns of activations for Chinese processing may have been linked to the logographic nature of Chinese characters (thus the right visual systems) and Chinese phonological processing or orthography-phonology transformation (OPT).…”
Section: Backward L2-to-l1 Switchingmentioning
confidence: 93%
“…Among these studies, six used an explicit, phonology-related decision task [Chen et al, 2002;Kuo et al, 2004;Siok et al, 2003Siok et al, , 2004Tan et al, 2001aTan et al, , 2003, two used reading aloud [He et al, 2003;Tan et al, 2001b], and one used silent reading [Kuo et al, 2001]. We decided to enter the data of the six studies employing an explicit phonological judgment task into the meta-analysis (Table I), and excluded the three studies with the silent-reading or reading-aloud paradigm, because we believed that reading aloud is relevant not only to phonological processes in visual character identification, but also to auditory and (passive) language production processes.…”
Section: Literature Selectionmentioning
confidence: 99%
“…In the last several years, neuroimaging investigations with Chinese characters have also been conducted, often with a focus on functional anatomy of phonological processing in reading [Chen et al, 2002;He et al, 2003;Kuo et al, 2004;Siok et al, 2003Siok et al, , 2004Tan et al, 2001aTan et al, , 2003. Some of these studies have implicated significant differences in neural bases for reading in Chinese and English.…”
Section: Introductionmentioning
confidence: 99%